1997
DOI: 10.1183/09031936.97.10040886
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum colonization, prematurity and bronchopulmonary dysplasia

Abstract: The aim of the present study was to determine the association between the presence of Ureaplasma urealyticum in endotracheal aspirates and bronchopulmonary dysplasia (BPD). In addition, a review of similar studies from the English literature is presented. During the period February 1990 until March 1991, 108 mechanically-ventilated infants were included in a prospective study. Endotracheal aspirates were cultured for U. urealyticum. Birth weight, gestational age and development of BPD was recorded. Cultures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[36][37][38][39] However, other studies showed there was no such association. 11,[40][41][42] A meta-analysis in 1995, pooled 13 studies and found a significant association between U. urealyticum and BPD. 43 Even with a more rigorous definition of BPD, a meta-analysis performed in 2005 found this association as well.…”
Section: Bronchopulmonary Diseasementioning
confidence: 99%
“…[36][37][38][39] However, other studies showed there was no such association. 11,[40][41][42] A meta-analysis in 1995, pooled 13 studies and found a significant association between U. urealyticum and BPD. 43 Even with a more rigorous definition of BPD, a meta-analysis performed in 2005 found this association as well.…”
Section: Bronchopulmonary Diseasementioning
confidence: 99%
“…The association between Ureaplasma and BPD was first discussed by Holtzman et al in 1989, who concluded that there was not enough evidence to prove the association [5]. Several studies also investigated the association between Ureaplasma and BPD, yielding conflicting findings [6][7][8][9]. Castro-Alcaraz and colleagues found the pattern of Ureaplasma colonization may be related to BPD, given that infants with persistent Ureaplasma had an increased risk of BPD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses ( 12 , 13 ) reported higher odds for BPD development in infants colonized with Ureaplasma spp. Studies included in these meta-analyses used the original definition of BPD as oxygen dependence at 28 days of life ( 12 , 13 ).…”
mentioning
confidence: 99%
“…Meta-analyses ( 12 , 13 ) reported higher odds for BPD development in infants colonized with Ureaplasma spp. Studies included in these meta-analyses used the original definition of BPD as oxygen dependence at 28 days of life ( 12 , 13 ). This definition has later been updated to reflect the increased survival of extremely premature infants that often need supplemental oxygen or respiratory support in the first weeks simply due to lung immaturity ( 14 ).…”
mentioning
confidence: 99%